Arquitetura da informação e usabilidade em ambientes informacionais digitais: avaliação da intranet da Creduni - Sousa, Emilia Augusta Alves de (2014)
The traditional process of information transfer is being gradually replaced by the transfer through networks of electronic communication, whose transformation brought a new look to the companies information age. Given the important role played by information in the business environment, managers are rethinking their management practices, adopting strategies for its dissemination among employees, adopting nowadays mainly web environment as a channel of interaction between individuals who are included in this environment, emerging concerns about the connectivity between users and system. In this sense, there is the Intranet, whose goal is to provide information in the digital environment for employees. Treading the perspective of information science, the principles of information architecture and usability guidelines, this research discusses the informational needs, interaction with users and structuring of information from the Intranet Creduni João Pessoa. The problem addressed was how to improve the Intranet to improve communication with employees, facilitating the dissemination of information on this business. Being the area of Information Science and uncertainties involved in the transformation of a learning society, the theme of this research has a key role in this context, since the consolidation of an information society, the democratization of aligned to its easy access information is fundamental. This is an exploratory and descriptive study of qualitative and quantitative nature, in which to evaluate the intranet interface, was considered the analytical method (heuristic evaluation ) and the method of usability testing (questionnaire ). After collecting and analyzing data to enumerate a list of informational barriers relating to usability and information architecture, weaving up suggestions for improvement for each of them, from the point of view of users and evaluators. Finally, we discussed the importance of considering quality requirements aiming to provide better satisfaction in this business environment interactions. Finally it was concluded that the intranet Creduni JP lacks quality requirements that provide better satisfaction in this business environment interactions.